Case Report: Middle lobe syndrome: a rare presentation in eosinophilic granulomatosis with polyangiitis - Maranini, Beatrice; Guzzinati, Ippolito; Casoni, Gian Luca; Ballotta, Maria; Lo Monaco, Andrea; Govoni, Marcello (Frontiers in Immunology, 2023)
Background: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a group of disorders characterized by necrotizing inflammation of small-and medium-sized blood vessels and the presence of circulating ANCA. Eosinophilic granulomatosis with polyangiitis (EGPA) is a systemic ANCA-associated vasculitis, characterized by peripheral eosinophilia, neuropathy, palpable purpuras or petechiae, renal and cardiac involvement, sinusitis, asthma and transient pulmonary infiltrates. Middle lobe syndrome (MLS) is defined as recurrent or chronic atelectasis of the right middle lobe of the lung, and it is a potential complication of asthma. Case presentation: Herein, we describe a case of MLS in a 51-year-old woman, never-smoker, affected by eosinophilic granulomatosis with polyangiitis (EGPA), presenting exclusively with leukocytosis and elevated concentrations of acute-phase proteins, without any respiratory symptom, nor cough or hemoptysis. Chest computed tomography (CT) imaging documented complete atelectasis of the middle lobe, together with complete obstruction at lobar bronchial branch origin. Fiberoptic bronchoscopy (FOB) revealed complete stenosis of the middle lobar bronchus origin, thus confirming the diagnosis of MLS, along with distal left main bronchus stenosis. Bronchoalveolar lavage (BAL) did not detect any infection. Bronchial biopsies included plasmacells and neutrophils infiltrate, only isolated eosinophils and no granulomas, providing the hypothesis of vasculitic acute involvement less likely. First line agents directed towards optimizing pulmonary function (mucolytics, bronchodilators and antibiotic course) were therefore employed. However, the patient did not respond to conservative treatment; hence, endoscopic management of airway obstruction was performed, with chest CT documenting resolution of middle lobe atelectasis.To the best of our knowledge, this is the first detailed description of MLS in EGPA completely resolved through FOB. Identification of MLS in EGPA appears essential as prognosis, longitudinal management and treatment options may differ from other pulmonary involvement in AAV patients.